Comparison Between the Wong Incision and Stromal Hydration of Corneal Incisions in Phacoemulsification - Raymond Nelson Regalado, MD; Jay Marianito Vicencio, MD; Ruben Lim Bon Siong, MD; Lee Verzosa, MD (Philippine Journal of Ophthalmology)
Objective: To determine the efficacy of the Wong incision in providing wound seal compared to stromal wall hydration in clear cornea phacoemulsification in cadaveric porcine eyes.